FORMATION OF THE QUALITY OF WHEAT BREAD ENRICHED WITH SESAME FLOUR - KOBASA, IGOR; VOROBETS МARIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The work is devoted to the study of the possibility of using sesame flour as a functional additive to the recipe composition of wheat bread. Based on the results of the study of organoleptic and physicochemical indicators of wheat bread samples containing 5, 10 and 15 % (wt.) of sesame flour, it is shown that replacing wheat flour with sesame flour improves the surface condition, the color of the crust and crumb, its porosity, elasticity, taste and aroma. The optimal mass fraction of the studied additive to the recipe composition of wheat bread was established, which is 10 % (wt.). Such a sample showed better overall acceptability compared to others, as well as to a sample of a standard product in the combined evaluation pattern test. It was found that the addition of sesame flour increases the acidity of wheat bread compared to the control sample by 0.6–0.8 degrees, which is probably due to the presence of a significant amount of unsaturated fatty acids in sesame. In order to assess the state and behavior of the dough during kneading, to determine its extensibility, elasticity and resilience, rheological studies were conducted - to establish the dependence of the viscosity of dough samples on the shear rate. It was shown that the most unstable is the dough sample based on wheat flour, which contains 5.0 % (wt.) sesame flour. The destroyed structure of such a dough sample is restored slowly and occurs in an incomplete volume. The highest rate of restoration of the dough sample structure is observed for the sample with a sesame flour content of 15 % (wt.). Based on the obtained data and representative studies of organoleptic indicators, wheat bread containing 10% (wt.) sesame flour can be recommended to consumers as a functional food product that allows enriching the body with unsaturated fatty acids, vitamins, minerals, and dietary fiber.